Peace and Violence in Islam: An overview of Some Muslim Perspectives - MEGA HIDAYATI (Fakultas Agama Islam Universitas Muhammadiyah Yogyakarta, 2016)
The issue of violence has always been existent in world religions including Islam. The image of Islam as a violent religion has been described in various media espe-cially in the case of terrorism. This phenomenon leads to questions on how issues of violence are conveyed in Islamic teachings and how they have been understood differently by Muslims. This article aims to answer such questions by discussing the duty of Muslims, jihad, spirit of the Qur’an, and interpretation issues. The writing found that overgeneralization of a particular case in Qur’anic stories occurred; differences in interpretation are caused by the limitation of human beings in viewing their present reality and the reality of the past; issues of violence in the Qur’an are inevitable since the Qur’an was revealed at a time of extensive violence throughout human life, while the spirit of Islam is in creating peace among fellow human being; and a number of Muslims regard the prophet Muhammad’s life time as the pinnacle of Islamic civilization. These findings lead to the conclusion that issues of violence in Islamic teachings are always interpreted differently in a variety of manners.